(untitled) (Research, Society and Development, 2022)
This article presents the essential singularities in the development of systematic reviews of the literature, as it adds research evidence to conduct clinical practice, adopts characteristic protocols and seeks to give coherence to a wide documental corpus referring to the anatomy of premolars, as they are considered difficult to be treated endodontically due to wide variations in apical morphology, shape, face and root canals. Objective: The objective of this study was to carry out a systematic review of the literature, evaluating national studies on the determinant aspect in the execution of endodontic treatment due to the specific anatomy of lower premolars, in order to better understand it. Materials and method: systematic literature review, through bibliographical research, in which twenty one studies were tracked in the Lilacs, PubMed, Scielo, Bvsalud, BBO Odontologia and Academic Google databases from 2011 to 2022. Results: with inclusion and exclusion criteria for articles and, above all, a careful analysis of the quality of the selected literature, there was no significant association between the number of roots and gender. Conclusion: the complex anatomy of the lower premolars is the reason for several cases of clinical frustration, considering the number of roots and the diversity of root canals and the difficulty of identifying them. In this sense, knowledge of dental anatomy and the use of diagnostic solutions are of enormous importance in terms of treatment efficiency.